2017
DOI: 10.1007/s00439-017-1843-2
|View full text |Cite|
|
Sign up to set email alerts
|

Expanding the genetic heterogeneity of intellectual disability

Abstract: Intellectual disability (ID) is a common morbid condition with a wide range of etiologies. The list of monogenic forms of ID has increased rapidly in recent years thanks to the implementation of genomic sequencing techniques. In this study, we describe the phenotypic and genetic findings of 68 families (105 patients) all with novel ID-related variants. In addition to established ID genes, including ones for which we describe unusual mutational mechanism, some of these variants represent the first confirmatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
123
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 45 publications
11
123
0
5
Order By: Relevance
“…All variants identified by the present study were found in patients of Middle East origin. Two of them were observed more than once (Figure ), and these 2 variants have previously been reported from Saudi Arab patients . This fact, along with our haplotyping data for carriers of the c.196delC variant (Figure S1A), supports the hypothesis of founder variants to contribute to NKX6‐2 ‐related disease .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…All variants identified by the present study were found in patients of Middle East origin. Two of them were observed more than once (Figure ), and these 2 variants have previously been reported from Saudi Arab patients . This fact, along with our haplotyping data for carriers of the c.196delC variant (Figure S1A), supports the hypothesis of founder variants to contribute to NKX6‐2 ‐related disease .…”
Section: Discussionsupporting
confidence: 85%
“…The clinical findings were rather uniform in our cohort of patients (Table ). Regarding age at onset and severity, our patients and most of those reported previously are highly similar . A notable exception are 2 families that carry the c.121A>T (p.(Lys41*)) variant.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As expected in a highly consanguineous population (we note that 33% of our cohort was non‐consanguineous but endogamy cannot be ruled out in those cases), recessive causes accounted for the majority. We have seen this pattern repeatedly across other genetically heterogeneous diseases of the eye (retinal dystrophy and cataract), as well as other organs (intellectual disability) . In their review, Williamson and Fitzpatrick suggested that some of the recessive causes ( C12orf57 and ODZ3 , specifically) remain unconfirmed .…”
Section: Discussionmentioning
confidence: 62%